Aggravation of atopic dermatitis caused by allergy to rubber chemicals. - Holm, E.A.; Pedersen, L.; Jemec, J.B.E. (European Journal of Pediatric Dermatology, 2001)
Allergy to rubber chemicals appears to be an increasing problem among adults, since rubber allergy was first described in the ’50ies. Recent studies have shown that allergy to rubber components may also be an increasing problem among children. We identified 4 children with atopic dermatitis who developed resilient aggravation of their dermatitis. They were all patch tested with the True Test standard series on the suspicion of an external cause for their deterioration. Positive reactions were found to: mercapto mix, mercaptobenzothiazol, and thiuram. On suspicion of contact allergy to rubber chemicals the patients were advised to eliminate or reduce contact with rubber, and, after this, their atopic dermatitis improved. An important aspect of atopic dermatitis management is the importance of possible underlying contact allergies when unexpected aggravation is seen in children with atopic dermatitis. In these cases the possible role of rubber chemicals as sensitizers should be considered in children. Children’s environment frequently contains rubber. Contact allergy to rubber constituents acquired privately in childhood may become a considerable health problem due to the ubiquitous nature of the allergens.